Democratic Values in Early Childhood Education. Core Curriculum Analysis - Natalia Stek-Łopatka (Maria Curie-Skłodowska University, Lublin, Poland, 2023)
Introduction: Changes taking place in Poland and in the world in recent years have made democracy one of the issues requiring constant monitoring. Despite its importance, it is still omitted in the context of educational practice - especially at the early stages of education, the existence of the need for democratic education among the youngest individuals subject to statutory education is denied. This contributed to the start of research on democratic values in early childhood education, which had not yet been analyzed in the context of the "new" core curriculum. Research Aim: The aim of the research was to identify and evaluate the effects of education related to democratic values in the core curriculum of general education for the first educational stage. Method: The method of data collection was the desk research and the method of data analysis - semantic content analysis focused on the explicit text. Results: The results showed that the requirements related to democratic values in the core curriculum for the first stage of education are very few and focus on the area of knowledge and skills, ignoring attitudes. Conclusion: Goals formulated in legal and educational documents are often deformed and are at risk of being omitted in educational practice due to the existence of an informal and hidden program, which in turn makes the shaping of conditions enabling a child to be an active citizen even more at risk.